A case of panic attack developing after THC‐O acetate inhalation using an e‐cigarette device - Norio Sugawara; Norio Yasui‐Furukori; Kazutaka Shimoda (Wiley, 2023)
Abstract Aim Tetrahydrocannabinol acetate (THC‐O) is a cannabinoid‐based product, and few medical studies have evaluated the effects of THC‐O on humans. Recently, e‐cigarettes have become popular among teenagers and young adults worldwide. However, there have been reports of people misusing this device as a delivery system for drugs of abuse. Case Presentation We herein report a case of panic attack after THC‐O inhalation using an e‐cigarette device in an 18‐year‐old male with no history of psychiatric disorders. Although he started smoking both regular cigarettes and e‐cigarettes in junior high school, he had never vaped delta‐9 THC or THC‐O until the present episode. A total of 20 min after his first inhalation of THC‐O, he experienced a sudden attack that lasted 2 h. After this episode, he did not inhale THC‐O. Throughout the subsequent 6 months of follow‐up, he maintained improvement with no panic attacks. Conclusion In this case, we intend to emphasize that THC‐O is not safe, even if the substance is regarded as loophole drug. The use of e‐cigarette devices might accelerate substance abuse.